Publisher Correction: Parent of origin genetic effects on methylation in humans are common and influence complex trait variation - Yanni Zeng (Nature Portfolio, 2019)
In the original version of this Article, the legend in the upper panel of Figure 2 incorrectly read ‘paternal imprinting’ and should have read ‘maternal imprinting’. This has been corrected in both the PDF and HTML versions of the Article.